Multiple target-based combination therapy of galantamine, memantine and lycopene for the possible treatment of Alzheimer's disease. (October 2020) - Vishwas, Sukriti; Awasthi, Ankit; Corrie, Leander; Kumar Singh, Sachin; Gulati, Monica
Abstract: Alzheimer's disease is type of dementia in which cognitive functions get declined. More than 50 million people are affected by this disease across the world. Many clinical and preclinical studies have been conducted on the treatment of AD but very limited number of drugs have found a clinical application. Because regeneration of neuron is a complicated process due to the involvement of multiple pathways, a combination of drugs that can work through multiple pathways could prove to be effective in treating AD. Based on prior studies and different mechanisms involved in the treatment, a new hypothesis has been proposed that a combination of galantamine, memantine and lycopene is anticipated to produce better activity as compared to the current therapies available in market for the treatment of this disease.